Do benevolent aspects have room explaining EU budget receipts? - Heikki Kauppi; Mika Widgrén (The Research Institute of the Finnish Economy (ETLA), 2008)
The member states have self-interested objectives and they use their voting power in the Council of Ministers (CM) to maximize their shares from the EU budget, whereas European Parliament (EP) uses its power to support benevolent objectives and equality between member states. Given the current decision procedures of the EU, EP has effective power on non-compulsory expenditure covering structural spending, but not on compulsory expenditure consisting mainly of agricultural spending. We use this fact to assess how the assumed benevolent objectives of EP turn into member states' budget receipts in a power politics based model.
Keywords: C71; D70; D72; 330; European integration; EU budget; voting power; EU-Finanzen; Politiker; Verhandlungsmacht; Eigeninteresse; EU-Staaten